2001
DOI: 10.1002/1521-3951(200111)228:2<445::aid-pssb445>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Luminescence Studies of Nitride Semiconductor Thin Films under Ambient Conditions

Abstract: We have investigated the properties of a commercial light-emitting diode (LED) structure containing an InGaN single quantum well (SQW) by scanning tunneling luminescence (STL). Data was acquired under ambient conditions, i.e., in air and at room temperature, using our unique STL microscope with a novel light collection geometry. Scanning tunneling microscopy (STM) images revealed the presence of hexagonal pits in the structure, with STL images showing strong luminescence from these pits. The variation of STL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Note that, previous STL microscopy studies in nitride devices showed luminescence intensity fluctuations over a typical scale of 100 nm. In these early experiments, structures were not compatible with high resolution because of thick injection layers (100 nm in [31], 200 nm in [32]) and multiple QW active region [31] or a single QW capped with a GaN/AlGaN barrier [32].…”
mentioning
confidence: 99%
“…Note that, previous STL microscopy studies in nitride devices showed luminescence intensity fluctuations over a typical scale of 100 nm. In these early experiments, structures were not compatible with high resolution because of thick injection layers (100 nm in [31], 200 nm in [32]) and multiple QW active region [31] or a single QW capped with a GaN/AlGaN barrier [32].…”
mentioning
confidence: 99%
“…[9] Another near-field technique based on scanning tunneling electroluminescence (STL) microscopy [10][11][12][13][14] was used to identify the origin of PL broadening in nitride materials. [15][16][17] However, experiments were performed on inappropriate heterostructures with multiple QWs or a single QW too far from the surface which led to degraded spatial resolution, allowing only for emission fluctuations at large spatial scales to be observed. More recently, STL has nonetheless shown its capability to assess smaller-scale sources of PL broadening.…”
Section: Introductionmentioning
confidence: 99%